2014
DOI: 10.1021/mz500090n
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of Hydrophobic and Hydrophilic Residues in Amphiphilic Polymer Coatings Affects Surface Structure and Marine Antifouling/Fouling Release Properties

Abstract: Amphiphilic polymers, specifically combinations of hydrophilic and hydrophobic residues, have been shown to be effective as antifouling materials against the algae Ulva linza and Navicula diatoms. Here we use the inherent sequence specificity of polypeptoids made by solid-phase synthesis to show that the sequence of hydrophilic (methoxy) and hydrophobic (fluorinated) moieties affects both antifouling and fouling release of U. linza. The platform used to test these sequences was a polystyrene-bpoly(ethylene oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
111
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 20 publications
3
111
0
1
Order By: Relevance
“…With the aim to develop films for AF/FR of marine species, a polystyrene‐ b ‐poly(ethyleneoxide‐ co ‐allylglycidyl ether) (PS‐P(EO‐ co ‐AGE)) block copolymer was functionalised via thiol‐ene click chemistry with a thiol‐terminated peptoid composed of the aformentioned fluorinated and methoxyethyl N ‐glycine residues (Figure ) . It was found that the number of the highly surface‐active fluorinated moieties influenced the surface composition as well as the AF/FR performance (Figure ).…”
Section: Amphiphilic Polypeptides and Peptide‐mimic Polymersmentioning
confidence: 99%
“…With the aim to develop films for AF/FR of marine species, a polystyrene‐ b ‐poly(ethyleneoxide‐ co ‐allylglycidyl ether) (PS‐P(EO‐ co ‐AGE)) block copolymer was functionalised via thiol‐ene click chemistry with a thiol‐terminated peptoid composed of the aformentioned fluorinated and methoxyethyl N ‐glycine residues (Figure ) . It was found that the number of the highly surface‐active fluorinated moieties influenced the surface composition as well as the AF/FR performance (Figure ).…”
Section: Amphiphilic Polypeptides and Peptide‐mimic Polymersmentioning
confidence: 99%
“…Other interesting alternative approaches to AF involve nontoxic polymer coatings that either deter the settling organism from adhering or weaken the interactions between the organism and the surface, allowing their removal via hydrodynamic shear forces . The promising recent developments of amphiphilic polymers made from copolymerised peptoids as fouling release coatings and also other hydrophobic coatings displaying linked quaternary ammonium groups suggest that the concept of cationic amphiphilic peptides may be display interesting AF properties in several areas Majumdar, Lee, Patel, Ward et al 2008;Martinelli et al 2011;Lejars et al 2012;van Zoelen et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…While the control of the microstructure of polymers still remains a challenge for polymer chemists, the ability to tune the sequence of polymers would be an asset for applications in materials sciences. For example, van Zoelen et al reported the preparation of sequence‐specific polypeptoids based on hydrophobic and hydrophilic units used as coating on a surface . The authors demonstrated that the sequence had an effect on the antifouling or fouling release properties of this coating.…”
Section: Introductionmentioning
confidence: 99%